Experimentos e experiências na sala de aula : potencialidades pedagógicas das atividades investigativas no ensino de física - Silva, Alexander Aparecido (2014)
The present study discusses the contribution of investigative activities in teaching physics to high school. While considering the polysemy around the definition of teaching for research, investigative activities taking proposals were developed based on principles and criteria which, in the view of the authors of reference, featuring investigative activities.Are analyzed the records produced by the students in the search for evidence to demonstrate the potential of investigative activities in relation to the integration of students in scientific culture, with regard tothe construction of physical concepts and the consistent use of scientific terms, seeking a rapprochement with the ideas of Vygotsky and Bakhtin. The analysis points to the significant contribution of investigative activities for communication between teacher and students and these among themselves, besides promoting the expansion of scientific language and autonomy in solving the problems posed.The notes present in this study reveal the significant contribution of the research to the subjects involved, which, in addition to the experiments, share an educational experience that opens avenues for future developments.